Integration of Religious and General Sciences as Solution to Face Globalization in Islamic Education Learning - Muhibbatul Karimah (Global Journal of Islamic Education, 2025)
Islamic education in Indonesia faces major challenges due to modernization and globalization that require adjustments without sacrificing traditional values. This article examines the concept and implementation of the integration of religious knowledge and general knowledge in Islamic Religious Education (PAI) learning as a strategic solution to face the challenges of globalization. The research methodology uses a qualitative approach with a literature study design, analyzing various sources to understand the challenges and solutions in integrating the two fields of knowledge. This study found that the integration of religious knowledge and general knowledge can strengthen the character and competence of students in facing the challenges of the modern world. The results of the study indicate the importance of developing a curriculum that integrates religious values with science and technology, as well as strengthening Islamic-based character education. In addition, approaches such as the spider web paradigm proposed by Amin Abdullah show great potential in creating a more holistic understanding of the world. This article provides recommendations for curriculum integration, teacher capacity building, and collaboration between educational institutions, government, and society to create competent, character-based graduates who are ready to compete in the global era. The novelty of this article lies in the curriculum integration approach based on a balance between religious knowledge and general knowledge, as well as the importance of strengthening character education in facing the dynamics of globalization.